GC-MS profiling and antidepressant-like effect of the extracts of Hamelia patens in animal model (Bangladesh Journal of Pharmacology, 2017)
Hamelia patens is used in folk medicine in the treatment of nervous shock. The present study deals to evaluate the antidepressant-like effects of chloroform and methanol extracts of H. patens on the performance of male mice and GC-MS profiling of bioactive extract. Mice were given extracts orally in acute doses of 100 and 200 mg/kg daily for 7 days and then subjected to forced swim test, tail suspension test and open field test. Imipramine (10 mg/kg/day, p.o.) and  fluxetamine (10 mg/kg/day, p.o.) were used as the standard in forced swim test and tail suspension test  respectively. GC-MS profiling of chloroform extract was performed to find out the chemical constituents in bioactive fraction. After one-week treatment, the chloroform extract (100 and 200 mg/kg/day, p.o.) significantly reduced immobility time in forced swim test and tail suspension test (p